Testing of Locally-made Ripening Room - Bundit Jarimopas; Prayouth Suwanchewakorn (Agriculture and Natural Resources, 1992)
Locally-made ripening room (LMR) of 240 cm. wide, 183 cm. long and 193 cm. high was evaluated for its performance. Results showed that temperature and humidity control function of LMR did not work properly. Insulation was too thin and temperature instrumentation was inefficient. Temperature variation was high as 6.6-11.8 degree C. Humidity control system could not be set to the desired level as 83% or less. Gas leakage out of the LMR room was high as 2.1 ml/min. Electrical power consumption was as 2.1-2.2 kw.